A mathematical high bar-human body model for analysing and interpreting mechanical-energetic processes on the high bar - Arampatzis, A.; Brüggemann, G. P. (Journal of Biomechanics, 1998)
The aims of this study were: 1. To study the transfer of energy between the high bar and the gymnast. 2. To develop criteria from the utilisation of high bar elasticity and the utilisation of muscle capacity to assess the effectiveness of a movement solution. 3. To study the influence of varying segment movement upon release parameters. For these purposes a model of the human body attached to the high bar (high bar-human body model) was developed. The human body was modelled using a 15-segment body system. The joint-beam element method (superelement) was employed for modelling the high bar. A superelement consists of four rigid segments connected by joints (two Cardan joints and one rotational-translational joint) and springs (seven rotation springs and one tension-compression spring). The high bar was modelled using three superelements. The input data required for the high bar human body model were collected with video-kinematographic (50 Hz) and dynamometric (500 Hz) techniques. Masses and moments of inertia of the 15 segments were calculated using the data from the Zatsiorsky et al. (1984) model. There are two major phases characteristic of the giant swing prior to dismountsfrom the high bar. In the first phase the gymnast attempts to supply energy to the high bar-humanbody system through muscle activity and to store this energy in the high bar. The difference between the energy transferred to the high bar and the reduction in the total energy of the body could be adopted as a criterion for the utilisation of high bar elasticity. The energy previously transferred into the high bar is returned to the body during the second phase. An advantageous increase in total body energy at the end of the exercise could only be obtained through muscle energy supply. An index characterising the utilisation of muscle capacity was developed out of the difference between the increase in total body energy and the energy returned from the high bar. A delayed and initially slow but even reduction of hip and shoulder angles provided more advantageous release conditions. The total body energy could be improved by up to 15%, the vertical CM release velocity by up to 10% and the angular momentum by up to 35%.